English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x^2/3 over x^1/2

2006-10-28 11:22:33 · 8 answers · asked by Kevin 5 in Science & Mathematics Mathematics

please explain or show work

2006-10-28 11:22:56 · update #1

8 answers

x^(2/3) / x^(1/2) = x^(2/3 - 1/2) = x^(4/6 - 3/6) = x^(1/6)

2006-10-28 11:28:29 · answer #1 · answered by Anonymous · 0 0

[x^(2/3)]/[x^(1/2)]
There are two ways to approach this, but it's really the same concept. You can solve it directly:
You are dividing x raised to some power by x raised to another power. When you have two exponential terms with the same base, in this case, x, and the operation is division, you can simply subtract the exponent of the term in the denominator, or bottom term, from the exponent in the numerator, or top term. So you'd have x^(2/3 - 1/2)=x^1/6.
The second approach is to look at the denominator. 1/(x^1/2)=x^(-1/2). When you multiply exponential terms with the same base, you add the exponents. So you still have x^(2/3 - 1/2)=x^1/6.

2006-10-28 18:31:58 · answer #2 · answered by Anonymous · 0 0

(x^2/3) / (x^1/2) = (x^2/3)(x^ -1/2)

When you multiply like terms with different exponents, you just add the exponents together. So taking the above into account...

(x^2/3)(x^ -1/2) = x^(2/3 - 1/2)

x^(2/3 - 1/2) = x^(4/6 - 3/6)

x^(4/6 - 3/6) = x^(1/6)

The answer is x^1/6

2006-10-28 18:27:07 · answer #3 · answered by robtheman 6 · 0 0

To do these manipulations, you will need to remember the exponent rules. Check your maths text book.

In this case x^a/x^b = x^(a -b). So

x^2/3 / x^1/2 =x^(2/3 - 1/2) = x^1/6

I assume your OK with the fractions otherwise

2/3 -1/2 =4/6 -3/6 =1/6

May the force be with you...

2006-10-28 18:30:52 · answer #4 · answered by A S 4 · 0 0

(x^2/3) / (x^1/2) = (x^2/3)(x^ -1/2)

(x^2/3)(x^ -1/2) = x^(2/3 - 1/2)

x^(2/3 - 1/2) = x^(4/6 - 2/6)

x^(4/6 - 2/6) = x^(2/6)

x^(2/6) = x^(1/3)

The answer is x^1/3

2006-10-28 18:31:32 · answer #5 · answered by pinkprincess 2 · 0 0

x^(1/6)

To solve:
(x^(2/3))/(x^(1/2))

Since your dividing terms with exponents, you subtract the exponent in the denominator from the exponent in the numerator.
(x^(2/3))/(x^(1/2))
x^((2/3)-(1/2))
x^(1/6)

2006-10-28 18:31:06 · answer #6 · answered by Bob 3 · 0 0

It all equals x. Srry I didn't show work but u put inverse exponents on other side of fraction is how you do it.

2006-10-28 18:26:07 · answer #7 · answered by Anonymous · 0 0

good question. lots of luck.

WOW~ you guys with the answer are smart!

2006-10-28 18:24:38 · answer #8 · answered by ndyou 3 · 0 0

fedest.com, questions and answers